Pengaruh Motivasi, Lingkungan Keluarga, dan Biaya Pendidikan terhadap Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi - Siti Nurhalizah; Argo Putra Prima (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research discusses students' interest in taking Professional Accounting Education (PPAk), this is important to do to increase interest in this education and make education more developed. Several factors that were taken into consideration in influencing this research were career motivation, family environment, and educational costs. This research uses a quantitative approach method which aims to determine the relationship between variables in an associative format involving two or more variables. The sample collection technique in this research used a survey and questionnaire instrument. The characteristics of the respondents in this study were students majoring in accounting in Batam City and registered in the DIKTI (Directorate General of Higher Education) database with a total of 3,456 students. Career motivation, family environment and educational costs simultaneously influence students' interest in taking Accounting Professional Education (PPAk). Career motivation has a significant effect on students' interest in taking Accounting Professional Education (PPAk), family environment does not have a significant effect on students' interest in taking Accounting Professional Education (PPAk), and cost of education has a significant effect on students' interest in taking Accounting Professional Education (PPAk).